How Do Reductions in Foreign Country Corporate Tax Rates Affect U.S. Domestic Manufacturing Firms? - Kim, Jaewoo; Nessa, Michelle; Wilson, Ryan J (The Accounting Review, 2021)
ABSTRACT We examine the effects of increased competition stemming from corporate tax rate cuts in foreign competitors' home countries on U.S. domestic manufacturing firms. We develop a measure of U.S. domestic firms' exposure to changes in foreign country tax rates and validate that the measure captures increased competition in the U.S. We find that, on average, U.S. domestic firms lose market power following declines in foreign country tax rates. We also find that, on average, U.S. domestic firms respond by increasing investment in research and development and capital expenditures and by improving total factor productivity. In cross-sectional analyses, we find the impact of foreign tax cuts is concentrated among U.S. domestic firms with low ex ante product differentiation. Taken together, these findings suggest that foreign country tax cuts escalate the competitive threat faced by U.S. domestic firms, and in response, U.S. domestic firms alter their investment strategies and/or become more productive. JEL Classifications: H2; H22; H25.